Lanskap Situs-Situs Obsidian di Kawasan Danau Bandung Purba, Jawa Barat - Nurul Laili; Rusyanti Rusyanti (PURBAWIDYA: Jurnal Penelitian dan Pengembangan Arkeologi, 2022)
This article aims to understand the landscape characteristics of obsidian sites around Bandung Basin area with its various dynamics as a form of cultural expression. This cultural expression relates to aspects of choosing a residential location and its relationship between sites, at a certain time. Through qualitative methods, descriptive reasoning and with a landscape approach and data collection techniques through geoarchaeological surveys and interviews, the 2021 research found 20 obsidian sites. The landscape in the Bandung Purba Lake area can be divided into two: hills (highlands) with an altitude between 684-1534 ms above sea level and lowlands with an altitude below 684 ms above sea level. The conclusion obtained from the landscape approach in the Bandung Purba Lake area show that people choose and utilize the environment, adapting in space and time.